Penilaian Tingkat Keberhasilan Reklamasi (Permen ESDM No. 7 Tahun 2014) Lahan Bekas Tambang Pit 1 PT Pipit Mutiara Jaya di Kabupaten Tana Tidung Kalimantan Utara - Inung Arie Adnyano (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2016)
Activities mining can make the impact to a land, so that needs to be done reclamation in an effort toincrease the quality of land and improvement of the conditions the former land of the mine. In thiseffort to ensure and provide an assessment and protecting the environment, after the mining activitiesPT Pipit Mutiara Jaya conducted activities arrangement and the land use former mine by means ofrevegetasi. The assessment of the level success reclamation use Permen ESDM No.7 2014 On theimplementation of the extension of reclamation and mine close in business activities minerals and coalmining the total value of Pit 1 is 67,82. So that the implementation of reclamation on land formermining PT Pipit Mutiara Jaya fall into the criteria and, namely result for reclamation received with aneed to to the repair Until it reaches > 80 that is good (in the reclamation acceptable).